PERLINDUNGAN HUKUM TERHADAP PEMUTUSAN HUBUNGAN KERJA PADA MASA COVID-19 PERSPEKTIF SIYASAH DUSTURIYAH - Muda, Rahmawati; Basri, Halimah (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2022)
This study aims to examine the legal protection of unilateral termination of employment during the Covid-19 pandemic from the perspective of Siyasah Dusturiah. The method used is literature research with a juridical and normative approach to syar’i. The results showed that one of the reasons for employers in terminating their employment was a decrease in turnover during the implementation of Large-Scale Social Restrictions (PSBB) as a government policy to minimize the spread of Covid-19. But regulatively, unilateral termination of employment is not allowed, and if under certain circumstances and forced to do so, then the employer must still fulfill the rights of workers in accordance with labor legislation. In the perspective of Siyasah Dusturiyah, the policy is one way to avoid greater mafsadat (ugliness), but this condition cannot be used as legitimacy for employers to unilaterally terminate employment, without going through negotiations to ensure that workers’ rights remain protected and fulfilled.